INTRODUCING GIS TO LEARNING AND STIMULATING INTERACTIVITY AMONG STUDENTS (PANGEEA, 2025)
Railway Technical College \"Unirea\" in Paşcani embarked on the ambitious two-year Erasmus KA220 project, \"GIS FOR GIST OF EUROPE,\" commencing in December 2022. This endeavor is significant for both the institution and the local community. The project focuses on using Geographic Information Systems (GIS) to study the impact of climate change on the European environment. Interactive GIS maps allow users to explore the regions most affected by climate change, assess its effects on biodiversity and natural resources, and develop strategies to mitigate these environmental challenges. Within the Erasmus+ initiative, \"GIS for Gist of Europe,\" GIS plays a central role, aiding urban planning, territorial development, and sustainable resource management. It also contributes to efficient communication networks and waste management systems. Project activities include online and in-person meetings, as well as Learning, Teaching, and Training (LTT) sessions. Key objectives involve creating two eLearning platforms, one with STEM educational resources featuring GIS maps and another for GIS training. The project fosters the advantages of GIS in data accessibility, correlation, and localized database creation. This project employing GIS will address climate change's impact on Europe, enhancing education and advancing climate-resilient strategies. The digitization of Geography remains pivotal in modern education and research, deepening our understanding of our ever-changing world.
Keywords: GIS FOR GIST OF EUROPE; Geographic Information Systems (GIS); climate interactive GIS maps; natural resources; urban planning; sustainable resource change; management; eLearning platforms; STEM educational resources; digitization of Geography